Rural-Urban Migration and the Expansion of Youths’ Begging in Jigjiga Town, East Ethiopia - Ahmed, Mohammed Jemal (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Nowadays migration has become the hot issue of the world and Africa in general and Ethiopia in Particular. However, a due attention has been given for international migration. The internal rural-urban migration has got less attention. But, currently, the internal rural-urban migration is increasing in Ethiopia in general and in Jigjiga town in particular and it has a significant impact on the socioeconomic development of the country. The main objective of this study is, therefore, to appraise the causes and course of flow of migrants from the surrounding rural area to Jigjiga town and assessing their economic activities mainly beginning at their destination, Jigjiga town. Using qualitative method, this paper has attempted to fill the gap in this regard. The data has been collected through interviews, FGD, observation and through text analyses. The findings of this study reveals that significant number youth migrants were refuge in Jigjiga town where they were tried to make a living through begging in the streets, at the gate of the mosques or going from house to house asking for food. These migrant beggars have also faced various challenges such as unwanted pregnancy, high child mortality, sexual harassment like rape and social segregation.